The changing geopolitics in the South Caucasus during the war in Ukraine: Chances and risks for the region - Ralph Wrobel (OrdnungsPolitisches Portal (OPO), 2023)
Since February 2022 - when Russia invaded the Ukraine - the geopolitical situation in the South Caucasus changed dramatically. On the one hand, EU sanctions on Russia made the "Middle Corridor" of the Chinese Belt and Road Initiative through the South Caucasus more attractive for China and Europe, on the other hand the "protective power" Russia is weakened by the war and the Western sanctions leaving a vacuum of power in the South Caucasus. As a result, Azerbaijan was able to reconquer the region Nagorno-Karabakh in September 2023 within a few days, only. Therefore, the region is still not more an unassailable Russian "backyard" or "sphere of interest" but place of a new "great game" of the main powers in the world. Beside Russia losing power - a slight rise of China can be observed while the West - U.S. and the EU - is still neglecting the region. Only Türkiye became a new active geopolitical player in the region. This may - beside all tragedy for the people of Nagorno-Karabakh - bring some "never ending conflicts" in the region to an end and may open up new opportunities for Armenia, Georgia and Azerbaijan to develop better economically in the near future.
Keywords: 330; Geopolitics; South Caucasus; Georgia; Armenia; Azerbaijan; EU; Belt & Road Initiative